Antimicrobial stewardship through a one health lens: Observations from Washington State. Issue 3 (5th September 2016) - D'Angeli, Marisa Anne; Baker, Joe B.; Call, Douglas R.; Davis, Margaret A.; Kauber, Kelly J.; Malhotra, Uma; Matsuura, Gregory T.; Moore, Dale A.; Porter, Chris; Pottinger, Paul; Stockwell, Virginia; Wagner, Carol; et al.
Abstract : Purpose: – Antibiotic resistance (AR) is a global health crisis that is attracting focussed attention from healthcare, public health, governmental agencies, the public, and food producers. The purpose of this paper is to describe the work in Washington State to combat resistance and promote antimicrobial stewardship from a one health perspective. Design/methodology/approach: – In 2014, the Washington State Department of Health convened a One Health Steering Committee and two workgroups to focus on AR, the One Health Antimicrobial Stewardship work group and the One Health Antimicrobial Resistance Surveillance work group. The group organized educational sessions to establish a basic understanding of epidemiological factors that contribute to resistance, including antibiotic use, transmission of resistant bacteria, and environmental contamination with resistant bacteria and antibiotic residues. Findings: – The authors describe the varied uses of antibiotics; efforts to promote stewardship in human, and animal health, including examples from the USA and Europe; economic factors that promote use of antibiotics in animal agriculture; and efforts, products and next steps of the workgroups. Originality/value: – In Washington, human, animal and environmental health experts are working collaboratively to address resistance from a one health perspective. The authors are establishing a multi-species resistance database that will allow tracking resistance trends in the region. Gaps include measurement of antibiotic use in humans and animals; integrated resistance surveillance information; and funding for AR and animal health research.